Adaptation of a cold vapour mercury analyser to flow injection analysis - Pasquini, Celio (Hindawi Publishing Corporation, 1988)
Minor modifications to a Coleman MAS-50A Mercury Analyser System allowed the determination of mercury by flow injection analysis. Using sample volumes of 600 μl it was possible to analyse up to 120 samples per hour, with a detection limit of 0.2 μg. l(-1) (120 pg) of mercury. The authors also report on a simple digestion procedure which replaces the time- and reagent-consuming EPA procedure, when the sample content permits.